Changes in forest floor and mineral soil carbon and nitrogen stocks in a boreal forest after clear‐cutting and mechanical site preparation. (14th May 2015) - Piirainen, S.; Finér, L.; Starr, M.
Summary Significant amounts of organic carbon (C) and nitrogen (N) are accumulated in soil in boreal forests. However, increased concern has been shown regarding the negative impacts of forestry operations on both the C sequestration and N stocks in soil. Changes in the C and N stocks in woody debris, forest floor and mineral soil (0–20 cm) were studied in Eastern Finland for 10 years after stem‐only clear‐cutting followed by soil harrowing. Samples were taken from the uncut forest and from the different microsites formed by the harrowing (ridges, furrows and undisturbed areas). Carbon and N from logging residues were not incorporated into the forest floor or mineral soil stocks to any great extent. After 5 years the C stock above the mineral soil was smaller (< 20%) in the treated area than in the uncut forest and after 10 years it was < 50% smaller. The corresponding N stock was marginally larger (< 5%) after 5 years, but smaller (< 20%) after 10 years. In the mineral soil there were no changes; only the furrows lost C and N when compared with the other microsites, but not when compared with the forest. Harrowing increased the spatial variation in the forest floor C and N stocks. The comparison of the N losses from the soil and logging residues and woody debris with the leaching losses, the amounts utilized by the regenerating vegetation or estimated to be immobilized by the stumps at the same site indicated that N which remained after the clear‐cutting was retained at the site. For a full understanding of the impact of such a disturbance on stocks at a site all significant fluxes and stocks would need to be monitored.